Gut–liver axis dysregulation and microbial dysbiosis in invasive liver abscess: a narrative review - Bai, Xiaoshuai; Wang, Zhen; Guo, Kai; Zhou, Ping; Shi, Lei (Frontiers in Immunology, 2025)
Invasive liver abscess (ILA) represents a formidable clinical challenge, characterized by rapidly evolving hepatic lesions and systemic dissemination. The gut–liver axis, a vital conduit for immune and metabolic regulation, has emerged as a central driver of its pathogenesis. This narrative review draws on insights from select transcriptomic, proteomic, metabolomic, and microbiomic studies, revealing how chronic antibiotic use, unhealthy diets, and lingering pathological conditions disrupt intestinal barrier integrity and perturb bile acid and short-chain fatty acid metabolism. This dysregulated microenvironment facilitates bacterial translocation into the liver, triggering a robust inflammatory cascade and the upregulation of virulence factors involved in capsule synthesis and biofilm formation. Evidence suggests microbial dysbiosis contributes to hepatic immune dysregulation. These insights pave the way for novel ILA interventions. This review offers original insights by critically integrating evidence from transcriptomic, proteomic, metabolomic, and microbiomic studies with GRADE-evaluated clinical data, proposing a novel bacteria–inflammation–virulence feedback loop and precision therapeutic frameworks that target the gut-liver axis, filling gaps in traditional ILA models and guiding future interventions.